Measurement model of project complexity for large-scale projects from task and organization perspective. Issue 3 (April 2015) - Lu, Yunbo; Luo, Lan; Wang, Hongli; Le, Yun; Shi, Qian
Abstract Large-scale projects have grown in size, quantity, and complexity; thus, measuring project complexity has become an integral part of project management. This study used the task and organization (TO) perspective to propose a measurement model of project complexity through hidden work that reflected the dynamic "emerging" effect of influencing factors on project complexity. TO measures were identified and mapped with attribute settings of ProjectSim software. The proposed TO measurement method was then expressed as hidden workload divided by direct workload. Overall, 12 hypotheses on the relationship between TO measures and hidden workload were put forth. The Shanghai World Expo construction project was chosen to test the synchronous relationship between hidden workload and project complexity as well as to validate the proposed method. The measurement method could truly reflect the project complexity and therefore can be used to manage the complexity of large-scale projects.